2014
DOI: 10.3171/2013.12.jns131595
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgery inhibition of the Notch signaling pathway in a rat model of arteriovenous malformations

Abstract: R adiosuRgeRy has been used to manage patients with cerebral arteriovenous malformations (AVMs) for more than 4 decades. 56 It offers an important option for patients with AVMs that are unsuitable for resection or embolization. 47,54 Studies reveal that radiosurgery induces thrombosis in AVM vessels, and by 2-3 years approximately 75% of AVM vessels are completely obliterated. 37,48,63 Although overexpression of endothelial adhesion and inflammatory and thrombotic molecules has been reported in irradiated endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 72 publications
(100 reference statements)
1
4
0
Order By: Relevance
“…Yu et al (46) recently reported that the activation of Notch1 and Hes1 is instrumental in withstanding myocardial I/R injury. Tu et al (47) previously demonstrated that the activated Notch signaling pathway has been involved in the arteriovenous lesions in mice in accordance with the present conjecture. The present findings suggested that the activation of the Notch pathway upregulated the eNOS expression and NO production and alleviated cerebral ischemic injury, resulting in cerebrovascular pathology and neurological disease.…”
Section: Discussionsupporting
confidence: 92%
“…Yu et al (46) recently reported that the activation of Notch1 and Hes1 is instrumental in withstanding myocardial I/R injury. Tu et al (47) previously demonstrated that the activated Notch signaling pathway has been involved in the arteriovenous lesions in mice in accordance with the present conjecture. The present findings suggested that the activation of the Notch pathway upregulated the eNOS expression and NO production and alleviated cerebral ischemic injury, resulting in cerebrovascular pathology and neurological disease.…”
Section: Discussionsupporting
confidence: 92%
“…Germline mutations in VOGM risk genes RASA1, EPHB4, ACVRL1, PTNPN11, and NOTCH1 have been reported in other Mendelian diseases featuring vascular phenotypes 25,27,109,110,[114][115][116] . RASA1 and EPHB4 encode interacting proteins mutated in CM-AVM type 1 and 2, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of emerging molecular targets in AVM, radiosurgery is seen to both induce thrombotic occlusion of nidus vessels in addition to inhibiting Notch1 and Notch4 signaling in endothelial cells [ 66 ]. Both increased and decreased Notch activity induce AVM formation in sporadic AVM and syndromic-type Alk1 knockout models, respectively [ 21 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%